Aridification Inhibits the Release of Dissolved Organic Carbon from Alpine Soils in Southwest China - Yanmei Li; Jihong Qin; Yuwen Chen; Hui Sun; Xinyue Hu (Soil Systems)
The alpine peatlands in western Sichuan Province are currently experiencing aridification. To understand the effects of aridification on the characteristics of organic carbon release from alpine soils, the soil in the northwest Sichuan Plateau was investigated. Soil columns were incubated under different moisture conditions in situ and in the laboratory, and ultraviolet-visible absorption spectroscopy and three-dimensional fluorescence spectroscopy were used to assess the soil dissolved organic carbon (DOC) levels. The results revealed that (1) the cumulative release of DOC from alpine soil in the northwest Sichuan Plateau decreased with decreasing moisture content. The cumulative release of soil DOC in the laboratory (0–5 cm soil reached 1.93 ± 0.43 g/kg) was greater than that from soil incubated in situ (0–5 cm soil reached 1.40 ± 0.13 g/kg); (2) the cumulative release of DOC in 0–5 cm soil exhibited the greatest response to changes in water content, and the cumulative release of DOC from the 0–5 cm soil layer (1.40 ± 0.13 g/kg) was greater than that from the 5–15 cm soil layer (1.25 ± 0.03 g/kg); and (3) UV-visible absorption spectra and 3D fluorescence spectral characteristics indicated that aridification increases the content of chromophoric dissolved organic matter (CDOM) components with strong hydrophobicity, especially tyrosine components (surface soil increased 39.59~63.31%), in alpine soil DOC. This increase in hydrophobic CDOM components enhances the aromaticity and degree of humification of DOC. Our results revealed that drought inhibits the release of soil DOC, which is unfavorable for the sequestration of organic carbon in alpine soils, potentially resulting in the loss of soil carbon pools and further degradation of alpine ecosystem functions.